2021
DOI: 10.21037/aol-20-52
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and magnetic resonance imaging in primary central nervous system lymphoma—a narrative review

Abstract: This review addresses the challenges of primary central nervous system (CNS) lymphoma diagnosis, assessment of treatment response, and detection of recurrence. Primary CNS lymphoma is a rare form of extra-nodal non-Hodgkin lymphoma that can involve brain, spinal cord, leptomeninges, and eyes. Primary CNS lymphoma lesions are most commonly confined to the white matter or deep cerebral structures such as basal ganglia and deep periventricular regions. Contrast-enhanced magnetic resonance imaging (MRI) is the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 142 publications
0
18
0
Order By: Relevance
“…Of these PCNSLs, diffuse large cell B-cell lymphoma of the CNS is the most common histologically defined tumor (Wang et al, 2021). PCNSL typically forms either single or multiple hypercellular, diffusely growing lesions (Krebs et al, 2021). Predominant perivascular aggregation, in the form of tight vascular cuffs of neoplastic cells intermingled with reactive non-neoplastic infiltrating inflammatory lymphocytes and macrophages, is typically detected at the periphery (Marcelis et al, 2020).…”
Section: Brain Lymphomamentioning
confidence: 99%
“…Of these PCNSLs, diffuse large cell B-cell lymphoma of the CNS is the most common histologically defined tumor (Wang et al, 2021). PCNSL typically forms either single or multiple hypercellular, diffusely growing lesions (Krebs et al, 2021). Predominant perivascular aggregation, in the form of tight vascular cuffs of neoplastic cells intermingled with reactive non-neoplastic infiltrating inflammatory lymphocytes and macrophages, is typically detected at the periphery (Marcelis et al, 2020).…”
Section: Brain Lymphomamentioning
confidence: 99%
“…Magnetic resonance spectroscopy in PCNSL lesions shows high Choline resonance (a cell membrane marker), a low N-acetylaspartate peak (a neuronal marker) and a large amount of mobile lipids [63]. Unfortunately, these findings are inconstant, nonspecific, and, to date, they do not provide survival information [64].…”
Section: Neuroradiological Featuresmentioning
confidence: 99%
“…In a retrospective analysis of 127 IC patient scans, Bataille et al reported nine cases of exclusively cortical lesions mimicking a meningioma [ 20 ]. Less frequent presentations involve the eyes, leptomeninges, spine, or vascular system [ 21 ]. Only 1% of PCNSL present with spinal involvement, which typically appears as a solitary infiltrative lesion with multifocal areas of contrast enhancement.…”
Section: Brain Imaging Features At Diagnosismentioning
confidence: 99%
“…On MRI, this subtype may appear as diffuse leukoencephalopathy or multiple small infarcts [ 21 ]. In IS patients, lesions are often multifocal, with nodular or peripheral ringlike enhancement reported in up to 75% of cases.…”
Section: Brain Imaging Features At Diagnosismentioning
confidence: 99%